Association Between Sleep Duration and Cognitive Frailty in Older Chinese Adults: Prospective Cohort Study - Ruixue Cai; Jianqian Chao; Chenlu Gao; Lei Gao; Kun Hu; Peng Li (JMIR Aging)
Abstract BackgroundDisturbed sleep patterns are common among older adults and may contribute to cognitive and physical declines. However, evidence for the relationship between sleep duration and cognitive frailty, a concept combining physical frailty and cognitive impairment in older adults, is lacking. ObjectiveThis study aimed to examine the associations of sleep duration and its changes with cognitive frailty. MethodsWe analyzed data from the 2008‐2018 waves of the Chinese Longitudinal Healthy Longevity Survey. Cognitive frailty was rendered based on the modified Fried frailty phenotype and Mini-Mental State Examination. Sleep duration was categorized as short (<6 h), moderate (6‐9 h), and long (>9 h). We examined the association of sleep duration with cognitive frailty status at baseline using logistic regressions and with the future incidence of cognitive frailty using Cox proportional hazards models. Restricted cubic splines were used to explore potential nonlinear associations. ResultsAmong 11,303 participants, 1298 (11.5%) had cognitive frailty at baseline. Compared to participants who had moderate sleep duration, the odds of having cognitive frailty were higher in those with long sleep duration (odds ratio 1.71, 95% CI 1.48‐1.97; PPP ConclusionsLong sleep duration was associated with cognitive frailly in older Chinese adults. These findings provide insights into the relationship between sleep duration and cognitive frailty, with potential implications for public health policies and clinical practice.